2019
DOI: 10.4300/jgme-d-18-00717.1
|View full text |Cite
|
Sign up to set email alerts
|

Rising to the Challenge: Residency Programs' Experience With Implementing Milestones-Based Assessment

Abstract: Background Changes to assessment efforts following the shift to milestones-based assessment in the ACGME Next Accreditation System have not been fully characterized.Objective This study describes themes in initial milestones-based assessment practices with the goal of informing continued implementation and optimization of milestones-based assessment.Methods Semistructured interviews were conducted with 15 residency program leaders in 6 specialties at 8 academic medical centers between August and December 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…We found that CCC members relied on assumptions about where an individual trainee should be based on time in the training program, rather than determining where they are performing. This practice is inconsistent with the intent of the Milestone framework and suggests that the ''benchmarking'' approach found by Dzara et al persists, 11 even after years of experience with the Milestones.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We found that CCC members relied on assumptions about where an individual trainee should be based on time in the training program, rather than determining where they are performing. This practice is inconsistent with the intent of the Milestone framework and suggests that the ''benchmarking'' approach found by Dzara et al persists, 11 even after years of experience with the Milestones.…”
Section: Discussionmentioning
confidence: 90%
“…For example, in 2016, Dzara et al conducted an interview-based study of program directors across multiple specialties to gather information about Milestone implementation. Among the findings, participants indicated that some programs relied on ''a benchmark approach to assigning Milestones levels,'' assuming time-based achievement in the absence of complete assessment data, 11 signaling a flawed interpretation of, or approach to, Milestone ratings. Furthermore, 3 additional studies, with the aim of examining response process evidence, [12][13][14] retrospectively analyzed Milestone ratings for groups of residents, using quantitative analyses of large data sets to infer how raters use Milestones in resident assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Further, ensuring the consistency and alignment between a program curriculum and the Milestones assessment is vital knowledge for faculty to understand how trainees’ learning is progressing. Of course, other factors may also make the Milestone assessment difficult for faculty such as obtaining reliable data on certain milestones in unsupervised practice, lack of milestones implementation guidance, and knowledge deficiencies of faculty and trainees in the understanding of the meaning of the competencies in the context of their specialty or the right time and point for measurement of performance [ 5 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The need for ongoing professional development and faculty training is highly emphasized to overcome obstacles and barriers for successful implementation of Milestones in the literature [ 18 , 19 ]. The results from our study also suggest that PDs/APDs and faculty evaluators need to be trained in the science of assessment and evaluation as well as the use of survey’s technology platform which would make it easier to use with the existing Milestones practices and be able to track the progress of their trainees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation